AWARENESS AND UTILIZATION OF ANTENATAL CARE SERVICE AND DELIVERY SERVICE IN A RURAL COMMUNITY, NORTHWESTERN NIGERIA - ABUBAKAR A; SAMBO MN; IDRIS SH (Ntec Specialist, 2011)
Background: The fifth Millennium Development Goal seeks to improve maternal health. One of its targets is to reduce the maternal mortality ratio by three quarters between 1990 and 2015. The maternal mortality rate in Nigeria is amongst the highest in the world estimated at 704 per 100 000 live births. Antenatal care presents an opportunity for recognition and appropriate intervention for some of causes of maternal mortality in developing countries especially in rural areas. Method: the study was a cross sectional descriptive study. A structured interviewer administered questionnaire was used to collect information on awareness and utilization of antenatal care services amongst women in the reproductive age group including attendant at last delivery in Bomo village, North Western Nigeria. Results: Two hundred and sixty women in the reproductive age group participated in the study. More than half of the respondents (58%) were 29years and below. All the women were aware about ANC services while 83% had used the ANC services during their previous pregnancy. However only 8% of the women were attended to by a skilled attendant at last delivery. More than half (58%) of the women delivered at home unattended to by anyone. Conclusion: there is a high level of awareness of antenatal care but a lesser utilization compared to knowledge and very low skilled attendance at delivery.